Cardiac 31P-MR-spectroscopy in myocardial insufficiency - Krahe, T; Schindler, R; Neubauer, S; Ertl, G; Horn, M; Lackner, K (1993)
The relative linear relationships of creatin phosphate/γ-adenosin triphosphate (PCr/ATP) and of phosphodiester (PDE)/ATP were measured in 38 normals and 27 patients with cardiac insufficiency using cardiac 31P-MR-spectroscopy. There was no significant difference between normals and those with dilated cardiomyopathy (19 cases) and severe aortic valve lesions (8 cases), irrespective of the clinical stage of the cardiac abnormality. Within subgroups of insufficiency there was a correlation between PCr/ATP and the severity of the disease with significant differences between mild and severe cardiac insufficiency. In 6 patients a significant rise in PC/ATP could be demonstrated following clinical improvement under drug therapy. There was no correlation between the relative linear relationship and the left ventricular ejection fraction.